Respostas autonômicas e hemodinâmicas ao treinamento de alta intensidade com kettlebell em mulheres jovens saudáveis - Alves, Sabrina Pereira (2020)
The cardiac autonomic modulation and hemodynamic response have been evaluated during effort and in the recovery phase after exercise, to evaluate the dose-response and effectiveness in providing these beneficial cardiovascular responses. Kettlebell traini